Genetically modified planet environmental impacts of genetically engineered plants - Stewart, C. Neal.; Oxford eBooks (Oxford : Oxford University Press, 2004)
'Genetically Modified Planet' reaches beyond rhetoric to describe the environmental science of genetically modified plants. Risks & benefits are compared, & future biotechnology designed for environmental improvement & eco-restoration is described.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Transgenic plants; Plant genetic engineering; Transgenic plants -- Ecology; Plant genetic engineering -- Environmental aspects; Electronic books